Wolfgang Amadeus Mozart’s Quartet for Flute and Strings in A major, K.298: Performance Practice and Interpretation - Janyarayachon, Sethapong; Dhamabutra, Narongrit (Rangsit Music Journal, 2022)
The study of The Quartet for Flute and Strings in A Major, K.298 composed by Wolfgang Amadeus Mozart, epitomizes one of the significant masterpieces for Flute chamber repertoires. To conduct research and analysis in string ensembles, integrated critical thinking patterns, exchange of perspectives and musical concepts acquired from consistent practices, these are the essential key factors leading to enhancement in performing arts. This research aimed to: 1) study the concept and the role of flute through patterns of performance, repertoires reflecting the composer’s perspectives in accordance with the the music era, and 2) analysis interpretation illustrating the improvement of performing techniques; therefore, this musical concept analysis will serve as the epitome that reflects the composer’s viewpoint on the identity of Flute that brings about the creativity in musical performance that all musicians can potentially integrate and adapt into their performing approaches. Not only does it establish musical sagacity, but it also creates an exemplar for musical arts, aesthetics study and educational purpose that could be used significantly as the iconic reference for further use.